2004
DOI: 10.1074/jbc.m312451200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Porcine Coagulation Factor VIII Domains Responsible for High Level Expression via Enhanced Secretion

Abstract: Blood coagulation factor VIII has a domain structure designated A1-A2-B-ap-A3-C1-C2. Human factor VIII is present at low concentration in normal plasma and, comparably, is produced at low levels in vitro and in vivo using transgenic expression techniques. Heterologous expression of B domain-deleted porcine factor VIII in mammalian cell culture is significantly greater than B domain-deleted human or murine factor VIII. Novel hybrid human/porcine factor VIII molecules were constructed to identify porcine factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 39 publications
4
94
0
Order By: Relevance
“…1) in the mammalian expression vector ReNeo has been described previously (27,28). These constructs contain nucleotide sequence between the A2 and ap-A3 domains encoding a linker region of human or porcine origin that includes the Arg-His-Gln-Arg recognition sequence for PACE/furin processing (29,30).…”
mentioning
confidence: 99%
“…1) in the mammalian expression vector ReNeo has been described previously (27,28). These constructs contain nucleotide sequence between the A2 and ap-A3 domains encoding a linker region of human or porcine origin that includes the Arg-His-Gln-Arg recognition sequence for PACE/furin processing (29,30).…”
mentioning
confidence: 99%
“…9 For many secreted proteins, transit from the endoplasmic reticulum to the Golgi apparatus is rate limiting and the primary determinants of this limitation are believed to be specific amino acid sequences within the molecule itself. 10,11 Using this knowledge, we and others have focused on the development of biobetter FVIII molecules and their implementation into gene transfer vectors that can be used in stem cell gene therapy applications. For example, it was shown by Kaufman et al that coexpression of von Willebrand factor results in the improved accumulation of recombinant FVIII in the culture medium of heterologous cells.…”
Section: Origins and Limitations Of Fviii And Fix Biosynthesismentioning
confidence: 99%
“…For example, we and others have shown that BDD p-FVIII is expressed at 10-fold or greater levels compared with BDD h-FVIII. 11,15,16 This led to the rationale of using a recombinant murine stem cell (␥-retrovirus) viral vector encoding BDD p-FVIII in HSCT gene therapy studies. These studies were highly successful with respect to the plasma FVIII activity levels achieved in transplanted hemophilia A mice conditioned with lethal or sublethal irradiation-based conditioning.…”
Section: Multipotent Adult Stem Cell Therapies: Hscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further study using porcine/human hybrids has localized certain protein sequences within porcine FVIII that confer this advantage, although additional studies will be necessary to characterize the mechanism. 10 Bioengineering rFVIII for high-efficiency production could potentially reduce costs and increase the availability of concentrates for therapy.…”
Section: Improved Production Efficiencymentioning
confidence: 99%